2018
DOI: 10.3390/ijerph15081582
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Type 2 Diabetes and Alzheimer’s Disease in a Pakistani Population

Abstract: The epidemic of type 2 diabetes mellitus (T2DM) and the possibility of it contributing to the risk of Alzheimer’s disease (AD) have become important health concerns worldwide and in Pakistan, where the co-occurrence of T2DM and AD is becoming more frequent. To gain insights on this phenomenon, a cross-sectional study was initiated. We recruited and interviewed 820 research participants from four cities in Pakistan: 250 controls, 450 T2DM, 100 AD, and 20 with both diseases. Significant differences between group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Our team recently published the results of a descriptive study of Pakistani patients with T2DM, which confirmed gender differences and suggested possible associations with environmental factors [1]. The present study extends those observations to investigate a pilot study of global gene expression patterns in the same patients, using microarrays coupled with Ingenuity Pathway Analysis (IPA) and followed by selective gene validation.…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our team recently published the results of a descriptive study of Pakistani patients with T2DM, which confirmed gender differences and suggested possible associations with environmental factors [1]. The present study extends those observations to investigate a pilot study of global gene expression patterns in the same patients, using microarrays coupled with Ingenuity Pathway Analysis (IPA) and followed by selective gene validation.…”
Section: Introductionsupporting
confidence: 76%
“…We randomly selected our study subjects from our previously reported cohort recruited from the out-patient departments of four different regional hospitals of Pakistan, i.e., Islamabad, Rawalpindi, Lahore, and Abbottabad (see details in [1]). The study was undertaken with the prior approval by the Howard University Institutional Review Board (IRB-17-MED-43), and the informed consent was obtained from volunteers as per the approval of the Institutional Review Board (IRB) of Atta-ur-Rahman School of Applied Biosciences (ASAB), National University of Sciences and Technology (NUST) (28/IRB; dated.…”
Section: Study Participants Ethics and Selection Of Participants Fomentioning
confidence: 99%
See 3 more Smart Citations